DNA Barcoding and Morphology of the Spine Bahaba, Bahaba polykladiskos (Actinopterygii, Sciaenidae), from Thailand and Borneo, with Notes on Its Taxonomic Status - Liu, Shu Hui; Soranuth, Sirisuay; Yeh, Wen Bin; Wu, Shih Chia; Jongkar, Grinang; Mok, Hin Kiu; Chang, Yen Wei (National Academy of Marine Research, 2025)
In this study, we examined the external morphology of croaker specimens with distinct golden body coloration collected from Thailand's Bang Pakong River, along with one specimen of the spine bahaba, Bahaba polykladiskos (Bleeker), from the Sibuti River Estuary in northern Sarawak, Borneo. These specimens differed in coloration from previous descriptions of Ba. polykladiskos, including the specimen from Borneo, but shared other morphological characteristics, particularly a longer interocular distance, that closely aligned them with Ba. polykladiskos. Phylogenetic analyses and species delimitation based on DNA analysis of the COI gene sequence confirmed that the golden colored croaker from the Bang Pakong River and Ba. polykladiskos specimens from Borneo are conspecific, forming a sister group to the Boeseman croaker, Boesemania microlepis (Bleeker). An exceptional laterodorsal enlargement of the swim bladder head in both Ba. polykladiskos and Bo. microlepis further supports their close phylogenetic affinities. This study also discusses the taxonomic status of Ba. polykladiskos, and the genera Bahaba and Boesemania.